2022
DOI: 10.30880/jtet.2022.14.01.001
|View full text |Cite
|
Sign up to set email alerts
|

TVET Student’s Perception on Digital Mind Map to Stimulate Learning of Technical Skills in Malaysia

Abstract: Digital mind map is a digital tool that is becoming increasingly popular in today’s pedagogical visual aids. However, few empirical studies have been conducted regarding Technical and Vocational Education and Training (TVET) student’s competencies on using digital mind map in learning of their technical subjects. Hence, this survey research was designed to investigate TVET student’s perceptions on the digital mind map to stimulate their learning of technical skills in Malaysian higher learning institutions. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Although this study was not conducted in the same field as the studies mentioned above, the results were parallel. The findings in the literature have shown that mind maps help students make their knowledge visible, show them how much they know, allow them to correct their mistakes in real-time, affect their attitudes positively, and turn into an activity that students find (Abd Karim & Mustapha, 2022;Çelik, 2016;Kemankaşlı, 2018;Sabbah, 2015), and leading them to become more attentive and willing, thus increasing the effect on cognitive development. It is thought that the usage of colors and support with shapes and images allows information to be recalled and knowledge to be visualized.…”
Section: Volleyball Knowledge Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this study was not conducted in the same field as the studies mentioned above, the results were parallel. The findings in the literature have shown that mind maps help students make their knowledge visible, show them how much they know, allow them to correct their mistakes in real-time, affect their attitudes positively, and turn into an activity that students find (Abd Karim & Mustapha, 2022;Çelik, 2016;Kemankaşlı, 2018;Sabbah, 2015), and leading them to become more attentive and willing, thus increasing the effect on cognitive development. It is thought that the usage of colors and support with shapes and images allows information to be recalled and knowledge to be visualized.…”
Section: Volleyball Knowledge Testmentioning
confidence: 99%
“…In the study by Şen and Çoban (2018) on the effects of the mind map technique used in violin education courses on the cognitive and psychomotor skills and attitudes of students, it was determined that the mind map technique was effective in the development of cognitive and psychomotor skills, and it increased the permanence of theoretical knowledge. Abd Karim and Mustapha (2022) conducted a study on the technical and vocational education and training of students by using digital mind maps. It was found that mind maps stimulated the learning of technical skills.…”
Section: Volleyball Skill Testmentioning
confidence: 99%
“…Previous research has discussed collaborative learning and e-learning learning methods separately [27], [51], but there is no systematic literature review that compares various types of collaborative learning and e-learning learning methods in a comprehensive manner [1], [4], [25]. Therefore, this article aims to provide a clear picture of the best collaborative learning and e-learning methods that can be implemented in a university environment [15], [30], [58].…”
Section: Introductionmentioning
confidence: 99%
“…Collaborative learning involves interaction between students, both through online and face-toface discussions, with the aim of building shared knowledge. On the other hand, e-learning allows students to study online, utilizing technology such as video, audio and other digital learning platforms [1], [26], [63]. The combination of these two methods can create an effective and efficient learning experience for students [7], [57], [34].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, WIL is flexible and transforms into other educational models, such as informal education or lifelong learning (Jeong & McMillan, 2015) WIL is widely used to include work experience in profession-based academic programs such as law, medicine, nursing, and engineering which may be practised after graduation (Abeysekera, 2006). The strengths of WIL are to produce potential graduates that are able to get a high paid occupation (Abd Karim & Mustapha, 2022). Also, they can seek a job that suits their competency since studying in the actual workplace (Govender & Wait, 2017).…”
Section: Introductionmentioning
confidence: 99%